Community Perception Relationships about ODF with open Defecation Habits in Mundu, Cirebon District - Lili Amaliah; Agus Supinganto; Joel Rey Ugsang Acob (Universitas STRADA Indonesia, 2022)
The annual report of Public Health Center in Mundu in 2018, for the environmental sanitation program in STBM activities, it can be seen that villages that are verified as Open Defecation Free are 0.00% or there are still no villages that are categorized as Open Defecation Free villages, which currently there are still many people who have defecation behavior haphazardly even though the STBM program has been implemented 100%. this study aims to determine the relationship between public perceptions of Open Defecation Free and open defecation habits. the type of research used is quantitative with a cross sectional study design. The sample in this study used a purposive sample of 100 respondents. Result: the results showed that there was a significant relationship between people's perceptions of Open Defecation Free and open defecation, namely the value of ρ value 0.01 with a value of α <0.05, which means 0.01 <0.05.